The Intention Principle and the Doctrine of Double Effect. (23rd June 2018) - Saemi, Amir
Abstract: It is commonly believed that the Doctrine of Double Effect (DDE) is identical with, or presupposes, the Intention Principle according to which an act can be impermissible if done with a wrongful intention. A main line of objections to the DDE, then, stems from the worry that the Intention Principle implausibly interiorizes the wrongness of an action. I will argue, first, that the DDE does not presuppose the Intention Principle, and, second, that intuitions brought against the Intention Principle do not warrant us to reject the DDE. Therefore, a main line of objections to the DDE is misguided.